EKSISTENSI LEMBAGA PENDIDIKAN DITINJAU DARI MUTU - Hardianto (Program Studi Manajemen Pendidikan, 2019)
Quality education is a necessity of today's society. Quality education is characterized by internal and external customer satisfaction with educational services. To achieve this quality can be seen from the perspective of the institution and the teacher's perspective. Quality educational institutions are institutions that are able to exist in the midst of competition. This existence can be achieved by an improved culture, improved structure, improved access to resources, improved systems and improved relationships with stakeholders. Qualified teachers are teachers who have been provided with teaching practice programs before becoming professional teachers and mastering certain skills. One of the skills is the mastery of various teaching methods. To achieve quality teachers, teacher competency must always be improved.